2021
DOI: 10.1111/jop.13217
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical administration of tacrolimus in oral lichen planus: An updated systematic review and meta‐analysis of randomized controlled trials

Abstract: Background: Symptomatic oral lichen planus is a common chronic T-cell-mediated disorder characterized by pain and inflammation. The meta-analysis aimed to compare and evaluate the effects and safety of tacrolimus for treating patients with symptomatic oral lichen planus.Methods: A comprehensive literature review was performed, including PubMed, the Cochrane Library, Embase, and Web of Science published up to and including December 2020. ClinicalTrials.gov was searched for ongoing trials. There were no restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
(235 reference statements)
2
4
0
Order By: Relevance
“…The previous interpretation was documented in the recent meta-analysis by Zhangci et al ( 2022), which reported that there was no difference in clinical resolutions between tacrolimus and corticosteroids and recommended the use of mucoadhesive carrier systems with a sustained release profile for improving the clinical outcomes [26], which were also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The previous interpretation was documented in the recent meta-analysis by Zhangci et al ( 2022), which reported that there was no difference in clinical resolutions between tacrolimus and corticosteroids and recommended the use of mucoadhesive carrier systems with a sustained release profile for improving the clinical outcomes [26], which were also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The pooled data from our meta-analysis shows that there is not sufficient evidence to prove that Tacrolimus is better in efficacy than other topical corticosteroids. Our study's findings are consistent with earlier systematic reviews and meta-analyses (Guo et al, 2015;Sridharan et al, 2021;Su et al, 2022).…”
Section: Recurrence Of Lesion At Follow-upsupporting
confidence: 92%
“…[10][11][12][13][14][15][16][17][18][19][20]22,23 The efficacy of topical calcineurin inhibitors in comparison to topical corticosteroids has been examined in four conventional meta-analyses. While three studies concluded that both therapies are similarly effective, 17,18,24 one report indicated that topical tacrolimus is superior compared to topical steroids. 16 In a metaanalysis of multiple interventions, tacrolimus showed the best clinical response and the best symptom-reducing effect when compared to placebo and other topical interventions, while dexamethasone had the best sign-reducing effect and showed the least adverse events.…”
Section: Discussionmentioning
confidence: 99%